A multicomponent Lattice Boltzmann model for multiphase convection, diffusion, and reaction in two dimensions - Parker, J. M. (Array, 2009)
Summary: The lattice Boltzmann method is a promising technique for modeling of multiphase fluids. In this paper, a multicomponent multiple-relaxation-time (MRT) model is developed for mass and momentum transport. In this model, diffusion of mass is defined in a fundamentally correct manner – gradients of chemical potential are the driving force for this movement. As a result, distinct fluid phases form or disappear as a result of diffusion toward a local chemical equilibrium. Numerical analysis of the model proves that the desired mass and momentum transport is being achieved and the multiphase performance of the model is tested numerically